Worldwide Burden of Gastric Cancer Attributable to Tobacco Smoking in 2012 and Predictions for 2020 - Peleteiro, B (2015)
Background: The heterogeneous patterns and trends in tobacco consumption contribute to regional and gender differences in the burden of gastric cancer attributable to smoking. Aims: To estimate the proportion and absolute number of gastric cancer cases that can be attributed to smoking in different countries, in 2012 and 2020. Methods: Population attributable fractions (PAFs) were computed for 118 countries, using data of smoking prevalence in 2002 and 2011 and published estimates of the magnitude of the association between smoking and gastric cancer, assuming a time lag of ≈10 years. Results: For men, the highest PAF estimates in 2012 were observed in Eastern Asia and the lowest in North America, whereas for women the highest were in Western Europe and the lowest in Africa. Very high Human Development Index (HDI) countries presented the lowest median PAF in men (very high vs. high, medium, and low HDI: 17.2 vs. 20.8 %, p = 0.014) and the highest median PAF in women (very high vs. high, medium, and low HDI: 4.3 vs. 1.8 %, p < 0.001). Estimates for 2020 show a decrease in median PAFs, but the estimated absolute number of cases attributable to smoking in the countries analyzed increased for men (≈154,000 vs. ≈160,000) and decreased for women (≈6200 vs. ≈5600).